2021
DOI: 10.1038/s41467-021-23201-0
|View full text |Cite|
|
Sign up to set email alerts
|

Perfluoroalkyl substance pollutants activate the innate immune system through the AIM2 inflammasome

Abstract: Perfluoroalkyl substances (PFAS) are widely used in various manufacturing processes. Accumulation of these chemicals has adverse effects on human health, including inflammation in multiple organs, yet how PFAS are sensed by host cells, and how tissue inflammation eventually incurs, is still unclear. Here, we show that the double-stranded DNA receptor AIM2 is able to recognize perfluorooctane sulfonate (PFOS), a common form of PFAS, to trigger IL-1β secretion and pyroptosis. Mechanistically, PFOS activates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 78 publications
4
75
0
Order By: Relevance
“…For example, elevated lysozyme activity, an antimicrobial enzyme and important biomarker of innate immune system function, has been reported in both mammalian and non-mammalian species exposed to PFAS ( Guillette et al, 2020 ; Peden-Adams et al, 2009 , 2008 ). Furthermore, in vivo and in vitro experiments have demonstrated that PFAS exposure can lead to severe inflammation in organs, including the liver, kidneys, and nervous system ( Qian et al, 2010 ; Dong et al, 2012 ; Qazi et al, 2013 ; Xing et al, 2016 ; Xu et al, 2019 ; Wang et al, 2021 ). Systemic inflammation can disrupt the integrity of the BBB through modification of tight junctions, endothelial damage, degradation of extracellular matrix components, and changes in astrocytes ( Varatharaj and Galea, 2017 ).…”
Section: Neurophysiological and Neurochemical Mechanisms Driving Pfas...mentioning
confidence: 99%
“…For example, elevated lysozyme activity, an antimicrobial enzyme and important biomarker of innate immune system function, has been reported in both mammalian and non-mammalian species exposed to PFAS ( Guillette et al, 2020 ; Peden-Adams et al, 2009 , 2008 ). Furthermore, in vivo and in vitro experiments have demonstrated that PFAS exposure can lead to severe inflammation in organs, including the liver, kidneys, and nervous system ( Qian et al, 2010 ; Dong et al, 2012 ; Qazi et al, 2013 ; Xing et al, 2016 ; Xu et al, 2019 ; Wang et al, 2021 ). Systemic inflammation can disrupt the integrity of the BBB through modification of tight junctions, endothelial damage, degradation of extracellular matrix components, and changes in astrocytes ( Varatharaj and Galea, 2017 ).…”
Section: Neurophysiological and Neurochemical Mechanisms Driving Pfas...mentioning
confidence: 99%
“…When dsDNA binds to the AIM2 receptor, ASC and pro-caspase-1 are recruited for inflammasome complex formation and activation ( 30 , 31 ). Previous studies have found that the AIM2 inflammasome induction in hepatocytes and macrophages participates in chronic liver diseases via the pyroptosis pathway ( 32 35 ). However, the mechanism of AIM2 inflammasome regulation is not well-studied.…”
Section: Inflammasome Biology and Activationmentioning
confidence: 99%
“…Assembly of the AIM2 inflammasome in KCs led to the processing of IL-1β and IL-18 in response to hepatitis B virus infection, aggregating the development of liver cirrhosis ( 34 , 101 ). Moreover, perfluorooctane sulfonate (PFOS), a chemical that causes chronic systematic inflammation, activated the AIM2 inflammasome via the Ca(2+)–PKC–NF-κB/JNK–BAX/BAK axis ( 35 ). In contrast, deletion of the AIM2 suppressed PFOS-induced inflammation and fibrosis in the liver and other organs ( 35 ).…”
Section: Inflammasome and Pyroptosis In Liver Fibrosismentioning
confidence: 99%
“…The pathogen DNA can be accumulating in the cytosol due to infection of the cell with viruses or they can be generated by degrading bacteria in the cytosol via action of GBPs and IRGB10 ( 73 76 ). Cell stress leading to the release of non-oxidized mitochondrial DNA can also activate the AIM2 inflammasome ( 83 ) ( Figure 1 ).…”
Section: Signal 2: Activation Of the Nlrp3 And Aim2 Inflammasomesmentioning
confidence: 99%